2017
DOI: 10.1158/0008-5472.can-16-3308
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Breast Cancer Characterization through Single-Cell Analysis of Tumor and Adjacent Normal Cells

Abstract: There is a need to individualize assays for tumor molecular phenotyping, given variations in the differentiation status of tumor and normal tissues in different patients. To address this, we performed single-cell genomics of breast tumors and adjacent normal cells propagated for a short duration under growth conditions that enable epithelial reprogramming. Cells analyzed were either unselected for a specific subpopulation or phenotypically defined as undifferentiated and highly clonogenic ALDH+/CD49f+/EpCAM+ l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Because gene expression in normal tissues shows interindividual variations due to SNP in the gene regulatory regions (27), we had recently proposed that normal cells from the same patient need to be used to determine cancer-specific gene expression changes (28). Although the use of cells from normal tissues adjacent to tumor is far from perfect because of cancer-induced field defects on adjoining cells (29,30), it is still better to use those cells or from the unaffected contralateral breast than normal cells from unrelated individuals as controls to identify cancer-specific gene expression changes.…”
Section: Individualizing Tumor Characterization Through Propagation Omentioning
confidence: 99%
“…Because gene expression in normal tissues shows interindividual variations due to SNP in the gene regulatory regions (27), we had recently proposed that normal cells from the same patient need to be used to determine cancer-specific gene expression changes (28). Although the use of cells from normal tissues adjacent to tumor is far from perfect because of cancer-induced field defects on adjoining cells (29,30), it is still better to use those cells or from the unaffected contralateral breast than normal cells from unrelated individuals as controls to identify cancer-specific gene expression changes.…”
Section: Individualizing Tumor Characterization Through Propagation Omentioning
confidence: 99%
“…scRNA-seq reports in the past years have provided useful information in this respect. Different types of CAFs have been reported in breast and colorectal tumors, which is likely to be associated with different cell origins [34][35][36]. Additionally, each group of CAFs has special functions in the recruitment of immune cells and in the induction of the epithelial-mesenchymal transition (EMT) in tumor cells [24,29,34,36].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…From a basic research point of view, results presented here provides an opportunity to determine whether a gene is truly differentially expressed in tumors compared to normal, as the expression pattern of a specific gene in the tumor could be a reflection of its cell-of-origin. Using single cell RT-PCR of tumor adjacent normal and tumor cells from the same individual, we had previously demonstrated that elevated expression of few genes in tumor can be attributed to cellof-origin of tumor instead due to tumor-specific genomic aberration (Anjanappa et al, 2017).…”
Section: Gene Signatures Of Epithelial Clusters and Their Relevance Tmentioning
confidence: 99%
“…While HER2+ breast cancers may originate from luminal progenitors and mature luminal cells, luminal-A/B breast cancers likely originate from mature luminal cells (Prat and Perou, 2009). However, it is acknowledged that heterogeneity exists within basal/stem, luminal progenitors and mature luminal cells as defined by CD49f/EpCAM cell surface marker profiling (Anjanappa et al, 2017;Colacino et al, 2018).…”
Section: Introductionmentioning
confidence: 99%